Spending behaviour among university students: case of Universiti Tunku Abdul Rahman (Kampar) - Chang, Lay Ying; Lim, Phui Mun; Teo, Yong Yee; Yau, Yan Yee; Yeoh, Yung Le (2019)
Today, the bankruptcy rate in Malaysia is rapidly increasing especially among youth. According the data provided by Malaysia Department of Insolvency, number of bankruptcy declaration is on an unstable upward trend since 2015. The population who declared bankruptcy and are below 25 is higher in 2018 compared to 2017, which shows the seriousness of this issue. Poor financial ability can lead to debt and overspending, which are the main causes of this phenomenon. And, since university students are the rising stars of a country, this study choose to focus on this group of people. This research examines what are the factors affect spending behaviour among university students in Universiti Tunku Abdul Rahman (UTAR), Kampar campus. This study consists of 4 independent variables, knowledge of financial management (KFM), parental income (PInc), peer influence (PI) and personality traits (PT): openness to experience, extroversion and agreeableness and are used to identify the relationship between spending behaviour among university students. 579 sets of questionnaires were analysed through Statistical Package of Social Science (SPSS) 19.0 software. According to results, all independent variables are found to have significant relationship with spending behaviour among university students, except for personality traits: agreeableness. This study also provides some recommendations and feedback on how overspending problem among university students can be reduced, especially for UTAR Kampar campus students. Therefore, this research will cover on the discussions of these factors and spending behaviour among university students.